Researching Interventions to Improve Medication Adherence in Ulcerative Colitis Patients - Pacheco, Mila Palma; Fortes, Flora Maria Lorenzo; Santos, Raquel Rocha dos; Silva, Genoile Oliveira Santana (Journal of Coloproctology, 2021)
The purpose of this review was to identify interventions that improve adherence to medications in patients with ulcerative colitis (UC). The literature search was carried out between April and June 2020 in the PubMed/MEDLINE database, with the combination of MeSH terms medication adherence; intervention; ulcerative colitis; and inflammatory bowel disease. We restricted our search to articles published in English and Portuguese between March 2010 and March 2020. After the selection, recovery of full-text articles and analysis of the defined criteria, the interventions described in the studies were classified into four domains: educational; behavioral, cognitive behavioral, and multicomponent. In total, six clinical trials met the inclusion criteria and were analyzed. Half of the studies (3; 50%) used multicomponent interventions, 2 (33.3%) focused on behavioral interventions, and 1 (16.7%) applied isolated educational interventions. All studies used indirect methods to measure adherence, with an emphasis on scales and questionnaires. Half of the studies (3; 50%) showed a positive impact on adherence in patients with UC, with evidence that multicomponent interventions, when properly implemented in a clinical trial combining direct and indirect methods to measure medication adherence, appear to increase the chances of better results. We believe that future studies focusing on improving adherence in patients with UC are necessary.
Keywords: medication adherence; colitis; ulcerative; inflammatory bowel diseases; self-management; drug therapy